Pregnant patient presenting with headache and medulloblastoma and hydrocephalous: a case report - Sharma, Swati; Tripathi, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Medulloblastoma, a primitive neuroectodermal tumor (PNET), is a second most brain tumor in children, accounting for about 20% of cases but is very rare in adults, 1% of all cancers in adults with only one third of cases occur in women and even less in pregnant women. It is primarily a cerebellar tumor. Symptoms include nausea, vomiting, loss of coordination, morning headache, seizures and personality changes. Treatment is surgical removal of tumor followed by radiotherapy. A grand-multipara presented in casualty with 30 weeks pregnancy & complains of headache, visual disturbances & disorientation. MRI findings were suggestive of medulloblastoma with hydrocephalus. Ventriculo-peritoneal shunting was done followed by termination of pregnancy. She delivered vaginally a live female child. After 15 days, her definitive neurosurgery was done. The uniqueness of this case is its rarity and symptoms of which are often masked by symptoms of pregnancy as syncope during pregnancy could be due to hypoglycemia, anxiety, orthostatic hypotension or cardiac causes.